The Effect of Chitosan Concentration as Binder on Electrical Conductivity of NaFePO4 for Application in Sodium Ion Battery Cathode - Tri Nugraheni (13314028), Nuurrisya Artinamuti (13314029), Nita
Limited lithium resources in the world pushes further research in battery technologies, especially on lithium alternatives. Abundant in nature sodium as the second lightest and smallest metal after lithium is a potential alternative to lithium. NaFePO4, the most promising cathode active material, is synthetized in this research. PVDF usage as cathode binder is expensive and not environmentally friendly, therefore it is replaced with chitosan. Synthesis of NaFePO4 as the cathode active material is done using the sol-gel and Pechini sol-gel methods because they are simple while able to produce particles with a small size. To increase conductivity, multi-wall carbon nanotube (MWCNT) is added to the active material. The effect of chitosan binder on conductivity is investigated by varying chitosan concentration with the values 0%, 2%, 4% 6%, 8%, and 10%. X-ray diffraction shows that the material NaFePO4 is successfully synthetized using the Pechini sol-gel method. Addition of chitosan as a binder increases the conductivity of cathode material. The highest conductivity of cathode material without MWCNT is 1,45·10-06 S/cm, achieved at 8% chitosan concentration. Addition of 3% MWCNT increases the overall conductivity of the cathode material. In the MWCNT added cathode material, increasing chitosan concentration reduces the conductivity with the highest conductivity value 1,69·10-03 S/cm at 2% chitosan concentration.